A novel integrated compensation method for actuator dynamics in real‐time hybrid structural testing. Issue 7 (27th September 2012) - Liu, Jie; Dyke, Shirley J.; Liu, Hong‐Jun; Gao, Xiu‐Yu; Phillips, Brian
SUMMARY Real‐time hybrid structural testing is a novel method that is gaining acceptance for examination of civil engineering structures. This method facilitates testing of an unknown physical component coupled with an analytical model of the remainder of the structure. A primary challenge in performing real‐time hybrid testing to accurately reproduce the behavior of the complete system is the appropriate compensation of actuator dynamics. Accounting for the magnitude roll‐off while also reducing the time lags to a minimal value is critical to ensure both accuracy and stability of a real‐time hybrid structural test. Here, a new compensation scheme is proposed that integrates the best features of two commonly used approaches. The proposed method, simply called integrated compensation, uses online delay estimation to improve on the performance of inverse compensation method for problems in which the effective time delay is not constant over the frequency band of interest. Two real‐time experiments are conducted to examine the capabilities of the approach for achieving good displacement tracking. Both experiments focus on the use of a device as the physical component. One experiment uses a linear spring as the physical component, and one uses a controllable, nonlinear damping device. The actuator displacement tracking results are compared with the results using other compensation approaches. The results from these experiments demonstrate that the proposed integrated compensation method is very effective and suitable for real‐time hybrid testing using a device as the physical component. Copyright © 2012 John Wiley & Sons, Ltd.